Demonstration of Urease Activity in Subgingival Plaque Sample of Periodontitis Patients in a Tertiary Care Center of Nepal - Lamichhane, Simant; Thapa, Sachita; Rijal, Arjun Hari; Marattha, Pratik; Humagain, Manoj; Rupakhety, Prakriti; Adhikari, Bhoj Raj (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Introduction: The urease activity is produced by many oral and gastric microorganisms, which have demonstrated systemic implications as well. Urea can be detected both from saliva and gingival crevicular fluid, which could suggest that the oral cavity can act as an extragastric reservoir for many microbes leading to serious systemic diseases. Objective: The main objective of this current study was to find out the urease activity in human dental plaque. Methods: An analytical cross-sectional study was conducted from September to November 2023 in patients visiting the Department of Periodontology and Oral Implantology. The urease activity was detected using a rapid urease test (RUT) kit from a hundred cases diagnosed with periodontitis. All systemically healthy patients excluding patients on ongoing proton-pump inhibitor therapy were selected for the presence/absence of periodontitis as per the 2017 World Workshop classification. Data were collected and entered into Microsoft Excel, and further analysis was done using SPSS v.20. Results: Out of 100 patients, urease activity was found positive in 85 (85%) patients. Regarding gender and age, the urease activity was not much different and was not statistically significant (P value= 0.163 and 0.382 respectively). Conclusions: The results of this study suggest there is a high urease activity in dental plaque samples whose removal is essential to prevent our body from systemic threats like bacterial endocarditis, gastric carcinoma, etc. caused by urease-producing microorganisms.